The full burn on the set, at the bar, behind the wheel, and over the edge with Hollywood stuntmen - Conley, Kevin 1960-
Journalist Kevin Conley takes readers inside one of the most fascinating and dangerous jobs in the world. With access to many of the legends of the field, including Uma Thurman's double for Kill Bill and the genius behind the Jason Bourne movies, Conley gives a passenger's-seat view of the stuntman's life: the history, the culture, and the tricks of the trade, showing how--and why--stuntmen do what they do. What's the greatest stunt ever performed? Why is the divorce rate among stuntmen so high? What's it like to go to work not knowing whether you'll come back? What's it like for your wife? What's the scariest trick a stuntman does? Conley delivers the answers in the form of vivid tales from his subjects' lives--and one from his own, when he subjects himself to the rite of passage known as the "full burn."--From publisher description.